Introduction to geographic information systems - Garcia, Jayceon (New York, NY Larsen & Keller, 2017)
The book aims to shed light on some of the unexplored aspects of geographic information systems (GIS). It provides thorough knowledge about the basic principles of this subject. Geographic information systems refer to a system that is used to manipulate, capture, store, analyze and maintain geographical data. The textbook covers the various fields that use this technology as well as the methods associated with it. It also focuses on the theoretical aspects on geographic information science. For someone with an interest and eye for detail, this book covers the most significant topics in this field. It will serve as a valuable source of reference for those interested in GIS.
Includes index.
Keywords: Geographic information systems; Information storage and retrieval systems -- Geography